TREATMENT OF CHRONIC EAR DISEASE - TOPICAL CIPROFLOXACIN VS TOPICAL GENTAMICIN - (:unkn) unknown (AMER MEDICAL ASSOC, 1995)
Objective: To determine and compare the therapeutic efficiency of ciprofloxacin hydrochloride and gentamicin sulfate in the treatment of chronic ear disease. Design: Prospective randomized study. Setting: Academic tertiary medical center. Patients: Consecutive referred sample of 44 patients with chronic suppurative otitis media randomized into two groups. Interventions: Ciprofloxacin hydrochloride (200 mg/mL) was administered to the first group (composed of 24 patients), while the second group (composed of 20 patients) received gentamicin sulfate (5 mg/mL) locally, five drops three times a day for 10 days. Results: In the ciprofloxacin group, 21 (88%) of the 24 patients with suppurative chronic otitis media were cured. On the other hand, only six (30%) of the patients in the gentamicin group were cured. The rest of the patients showed no clinical or bacteriological improvement. Conclusions: To our knowledge, this is the first study to compare the efficiency of two topical otic preparations in the treatment of chronic ear disease. The results show that topical ciprofloxacin preparation is more efficacious and efficient than topical gentamicin for the treatment of chronic otitis media in the acute stage.
Keywords: CHRONIC OTITIS-MEDIA; ORAL TREATMENT; INFECTIONS